1991
DOI: 10.1126/science.1909456
|View full text |Cite
|
Sign up to set email alerts
|

Anti-HIV and Anti-Anti-MHC Antibodies in Alloimmune and Autoimmune Mice

Abstract: Alloimmune mice (mice that have been exposed to cells from another murine strain) were shown to make antibodies against gp120 and p24 of human immunodeficiency virus (HIV), and mice of the autoimmune strains MRL-lpr/lpr and MRL-(+)/+ made antibodies against gp120. This is surprising because the mice were not exposed to HIV. Furthermore, anti-anti-MHC antibodies (molecules that have shapes similar to those of major histocompatibility complex molecules) were detected in both alloimmune sera and MRL mice. These r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
44
1

Year Published

1991
1991
2003
2003

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(49 citation statements)
references
References 19 publications
3
44
1
Order By: Relevance
“…A reagent that could permit the detection of such anti-center pole antibodies is gpl20. We found that anti-gpl20 antibodies can indeed be detected in hyperimmune alloantisera (44). Since the mice have never been immunized with gpl20, a reasonable interpretation is that the anti-gpl20 antibodies are anti-MHC-image antibodies.…”
Section: Aniti-hiv and Mhc-image Antibodies In Aflonimune Micementioning
confidence: 62%
See 1 more Smart Citation
“…A reagent that could permit the detection of such anti-center pole antibodies is gpl20. We found that anti-gpl20 antibodies can indeed be detected in hyperimmune alloantisera (44). Since the mice have never been immunized with gpl20, a reasonable interpretation is that the anti-gpl20 antibodies are anti-MHC-image antibodies.…”
Section: Aniti-hiv and Mhc-image Antibodies In Aflonimune Micementioning
confidence: 62%
“…We also see anti-p24 antibodies in murine alloimmune sera (44). In view ofevidence of similarities between class II MHC and each of gpl20, gp4l, and Nef, it is possible that the anti-p24 activity is also due to crossreactivity between p24 and class II MHC image.…”
Section: Aniti-hiv and Mhc-image Antibodies In Aflonimune Micementioning
confidence: 68%
“…Because the conserved domain of the envelope proteins of HIV-1 and HIV-2 are weakly immunogenic in native envelope configuration (36) Considering possible immune enhancement phenomena by antibodies against various epitopes of HIV envelope glycoproteins (38,39) and the superantigen and autoimmunity theories to explain the depletion of uninfected CD4-positive T lymphocytes (40,41), the chimeric gag virus-like particles provide an attractive option to develop a recombinant subunit vaccine using defined epitopes that can induce humoral and cell-mediated immunity against HIV infection.…”
Section: Discussionmentioning
confidence: 99%
“…Sequence similarities have been reported between major histocompatibility complex (MHC) class II, particularly HLA-DR and HLA-DQ, and gpl20 (18,19), HIV-1 Nef (20) and gp4l (21), and between the major retroviral capsid protein (CA) and regions in the Sm-BB' autoantigen, the SSB/La antigen, the 70-kDa ribonucleoprotein, topoisomerase I, and acetylcholine receptor (22,23). Finally, Hoffman and colleagues (24,25) struction of IgG1 K/A Fab libraries using the pComb3 M13 surface display system have been described (27,28,32).…”
mentioning
confidence: 99%